Implementation of a routine outcome monitoring and feedback system for psychotherapy in Argentina: A pilot study - Gómez-Penedo, Juan Martín; Manubens, Rocio; Areas, Malenka; Fernández-Álvarez, Javier; Meglio, Manuel; Babl, Anna; Juan, Santiago; Ronchi, Agnese; Muiños, Roberto; Roussos, Andrés; Lutz, Wolfgang; grosse Holtforth, Martin (Frontiers in Psychology, 2023)
Routine Outcome Monitoring (ROM) has emerged as a strong candidate to improve psychotherapy processes and outcome. However, its use and implementation are greatly understudied in Latin-America. Therefore, the aim of the present pilot study conducted in Argentina was to implement a ROM and feedback system grounded on a psychometrically sound instrument to measure session by session outcome in psychotherapy. The sample consisted of 40 patients and 13 therapists. At baseline, the patients completed the Patient Health Questionnaire-9 and the Generalized Anxiety Disorder-7, and they also completed the Hopkins Symptom Checklist-11 before each of the first five sessions. To estimate patient change during the first sessions, we conducted a quantitative analysis using Hierarchical Linear Models. Furthermore, we conducted a qualitative analysis using Consensual Qualitative Research to analyze therapist perception regarding the ROM and feedback system. Results showed a significant reduction in patients’ symptomatic severity during the first five sessions. Additionally, baseline depression significantly predicted the estimated severity at the end of the fifth session. Feedback was given to the therapists after the first four sessions based on these analyses. With regard to the perception of the feedback system, clinicians underlined its usefulness and user-friendly nature. They also mentioned that there was a match between the information provided and their clinical judgment. Furthermore, they provided suggestions to enhance the system that was incorporated in a new and improved version. Limitations and clinical implications are discussed.